Excipients for Cerium Dioxide Nanoparticle Stabilization in the Perspective of Biomedical Applications - Svetlana A. Titova; Maria P. Kruglova; Victor A. Stupin; Natalia E. Manturova; Raghu Ram Achar; Gouri Deshpande; Vladimir A. Parfenov; Ekaterina V. Silina (Molecules)
Rare earth metal nanoparticles, some of which are already widely used in medicine, are of growing interest in the modern scientific community. One of the promising rare earth metals for biomedical applications is cerium, specifically its oxide form, which is characterized by a higher level of stability and safety. According to a number of studies, cerium dioxide has a wide range of biological effects (regenerative, antimicrobial, antioxidant, antitumor), which justifies the interest of its potential application in medicine. However, these effects and their intensity vary significantly across a number of studies. Since cerium dioxide was used in these studies, it can be assumed that not only is the chemical formula important, but also the physicochemical parameters of the nanoparticles obtained, and consequently the methods of their synthesis and modification with the use of excipients. In this review, we considered the possibilities of using a number of excipients (polyacrylate, polyvinylpyrrolidone, dextran, hyaluronic acid, chitosan, polycarboxylic acids, lecithin, phosphatidylcholine) in the context of preserving the biological effects of cerium dioxide and its physicochemical properties, as well as the degree of study of these combinations from the point of view of the prospect of creating drugs based on it for biomedical applications.